Optimizing the Secure Key Rate of a Single Sequential Quantum Repeater with Two Different Quantum Memories - Khaled, Marwa A.; Hasan, Jawad A. (Iraqi Journal of Laser, 2020)
Quantum channels enable the achievement of communication tasks inaccessible to theirclassical counterparts. The most famous example is the distribution of secret keys. Unfortunately, the rateof generation of the secret key by direct transmission is fundamentally limited by the distance. This limitcan be overcome by the implementation of a quantum repeater. In order to boost the performance of therepeater, a quantum repeater based on cut-off with two different types of quantum memories is suggestd,which reduces the effect of decoherence during the storage of a quantum state.